Computer search for graceful labeling: a survey - Ljiljana Brankovic; Michael J. Reynolds (Electronic Journal of Graph Theory and Applications (EJGTA), 2022)
This paper surveys the main computer search results for finding graceful labeling of trees. The paper is devoted to the memory of Mirka Miller, who made an outstanding contribution to the area of graph labeling.